(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The increase in incidence, chronic relapsing course, and insufficient effectiveness of existing methods of treatment and prevention place brucellosis among the most pressing problems of human infectious pathology. It is noted that in terms of its distribution and socio-economic significance, this disease occupies one of the first places among zoonoses [1,5,9]. Features of the life cycle of Brucella and the infectious-allergic nature of brucellosis allow us to state the leading role of immune disorders in the pathogenesis of this disease. At the same time, many aspects of the immunology of brucellosis, in particular the features of intercellular relationships in the process of formation of anti-infective immunity in this pathology, have not been sufficiently studied, which does not allow the full use of the assessment of the immune status of patients with brucellosis to predict the chronicity of this infection [12,13,19]. The discovery of biologically active substances - cytokines, regulating the proliferation and level of functional activity of cells, both normally and in pathology, allows us to evaluate from a new perspective the mechanism of formation of inflammatory reactions, allergic and immune conditions and to develop new methods for predicting the nature of an infectious disease. Meanwhile, in the available literature, the role of cytokine metabolism disorders in brucellosis has not received sufficient coverage, which determines the relevance of research conducted in this direction. The discovery of biologically active substances - cytokines, regulating the proliferation and level of functional activity of cells, both normally and in pathology, allows us to evaluate from a new perspective the mechanism of formation of inflammatory reactions, allergic and immune conditions and to develop new methods for predicting the nature of an infectious disease. Meanwhile, in the available literature, the role of cytokine metabolism disorders in brucellosis has not received sufficient coverage, which determines the relevance of research conducted in this direction.